Computerized System to Manage Business Functionalities for a Gymnasium - T.C.M. Gamage; U.A.C.L. Jayasinghe; P.K.R.B. Premadasa; D.A.C.T. Dombepola; D. I. De Silva; R.R.P. De Zoysa (International Journal of Engineering and Management Research, 2022)
Sri Lanka as a still developing country must keep up with modern technologies. Computers in this advanced world are more and more famous and turning essential to our way of life. In these modern days, people are very much concerned about their health and diet, also they are looking for a gym. This Gymnasium management system is a combination of wellness centers designed to deal with customers easier and more efficiently. A gymnasium is a must-go place for any person who loves to live a fit and healthy bodybuilding lifestyle. This system is developed for Fitness Factory Gymnasium located in the Galle district in Sri Lanka. The gym is equipped with all modern machinery and other supporting items to provide better service to its customers. So, the number of members is increasing day by day and the gym management has decided to move to an IT solution to handle the increasing volumes. Improvement was finished after distinguishing client needs utilizing different information assortment innovations. Because of the prerequisites, the product was planned and created with an iterative and steady advancement technique. The system was created determined to supplant the ongoing manual framework utilized in the fitness center. The framework expresses that the fitness center's assets ought to be effectively available to its individuals while engaging the fitness center's administration cycle. Key functions such as trainer’s membership management, customer management, workout plans management (workout management), Customer workout schedule management, Nutrition plan management (Customer meal management), trainer leave management, Q & A management, BMI Calculator, memo and reminder management, inquiry management and report generation were identified. Access control is achieved with a username and password to the admin, trainer, and customer. The system can suggest the best workout schedules for the members. Researchers’ primary goal in developing this system is to make things that were previously done manually in the gym easier. Researchers expect that all system users will benefit from a better service.